Non-English Speaking Background (NESB) Students’ Perceptions of their Linguistic and Educational Needs - Briguglio, Carmela (IDP EDucation Australia, 1998)
NESB students' perceptions of their linguistic and educational needs and the availability of support structures to meet such needs are crucial to their improvement in academic performance and success in the tertiary system. While a number of surveys have been undertaken at Curtin University to gauge NESB student satisfaction with their courses and university services, it was felt that in-depth interviews with a small group of students would provide a more detailed picture of student needs. Eighteen NESB students, both local and international, were interviewed in some depth for this project. While the results indicate a high level of satisfaction with academic and other services provided by Curtin, they also point to some very clear areas for improvement. In particular, students indicated they require: various forms of English language support; encouragement to help them to mix more with Australian students, both in order to learn about Australian culture and to become more proficient in English; and staff who are more attuned to their linguistic and cultural needs and who can better provide for them.